Effect modification by sex of genetic associations of vitamin C related metabolites in the Canadian Longitudinal study on aging - Lelievre, Rebecca; Rakesh, Mohan; Hysi, Pirro G.; Little, Julian; Freeman, Ellen E.; Roy-Gagnon, Marie-Hélène (Frontiers in Genetics, 2024)
Vitamin C is an essential dietary factor. There have been observed sex differences in serum vitamin C concentrations but the reason for this is not fully known. To understand how environmental factors like vitamin C intake interact with molecular processes, levels of metabolites can be used. Two metabolites associated with vitamin C are O-methylascorbate and ascorbic acid 2-sulfate. Past research has found there are genetic factors that influence these metabolite levels. Here, we aimed to investigate if there is effect modification by sex of these genetic variant-metabolite associations and characterize the biological function of these interactions. We included individuals of European descent from the Canadian Longitudinal Study on Aging with available genetic and metabolic data (n= 9004). We conducted a genome wide association study with and without a sex interaction using mixed linear models. We also investigated the biological function of the important genetic variant-sex interactions found for each metabolite. Two genome-wide statistically significant (p-value < 5x10 -8 ) interaction effects and several suggestive (p-value < 10 -5 ) interaction effects were found. The suggestive interaction associations were mapped to several genes including HSD11B2, which is associated with sex hormones and AGRP that helps initiate hunger drive. By understanding the genetic factors that impact metabolites associated with vitamin C, we better understand its function in disease risk. In addition, highlighting genetic markers and genes whose effects are modified by sex can help to understand the mechanisms behind sex differences in vitamin C levels and guide further research.